Memahami Makna Ruang Melalui ‘SIMPUKNG’ - Ridjal, Abraham Mohammad (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2015)
Nature of the Nusantara archipelago with the composition of the ocean and the land has formed a diverse culture and architecture that characterizes all the archipelago's. Archipelago architecture has a form and concept are very diverse, ranging from simple to very complex. One of the underlying architecture embodiment of the archipelago is the conception of space. Diverse groups of people have a variety of concepts of space different, but with the sole purpose of creating archipelago nature and society for the better. One of them is 'simpukng' conception of the public space Benuaq governing society and the environment proxies in order to stay awake and well ordered. Simpukng concept is not only applied in the scientific community architecture Benuaq, but the concept of this space is used in almost all activities of the local people there. Therefore, in studying interdisciplinary required in order to obtain a more comprehensive understanding about this simpukng. One that can be learned from simpukng in architecture today is how to formulate the space, both micro and macro in formulating a sustainable overall concept, not partially.Keywords: Simpukng, Benuaq, space, architecture now, sustainable